A Theoretical Framework for Ethical Decision-Making During Public Health Emergencies - Ekmekci, Perihan Elif; Folayan, Morenike Oluwatoyin (Acta Bioethica, 2022)
The new theoretical ethical framework is a general frame or tool for ethical agents, developed to guide ethical reasoning during public health emergency preparedness and response. The TEF is based on the assumption that no existing ethical discourse in medical ethics alone is sufficient to address ethical issues of a PHE. The solutions suggested by existing approaches are limited in practicability and effectiveness, because they cannot address root problems and interplay among ethical problems. The reason for this insufficiency rests on the argument that ethical problems of PHEs have causal and reciprocal relationships, and any ethical decision-making framework should provide a wide enough perspective to consider relevant ethical norms and theories to suggest practical, implementable, coherent solutions compatible with the communal values and cultural norms. The TEF we suggest for PHEs embraces a holistic and integrated ethical perspective that enables us to comprehend that ethical problems that arise in various settings caused by PHE phenomena are in relationship with each other instead of addressing them as a standalone problem. The TEF provides decision-makers to achieve a coherent web of considered judgements compatible with ethical values and principles in various settings. This type of conceptualization offers a wide perspective to see causal and relational relationships among problems and produce outcomes that would not be possible by eclectic approaches.